The Hydrophobin-Like OmSSP1 May Be an Effector in the Ericoid Mycorrhizal Symbiosis - Casarrubia, Salvatore; Daghino, Stefania; Kohler, Annegret; Morin, Emmanuelle; Khouja, Hassine-Radhouane; Daguerre, Yohann; Veneault-Fourrey, Claire; Martin, Francis M.; Perotto, Silvia; Martino, Elena (Frontiers in Plant Science, 2018)
Mutualistic and pathogenic plant-colonizing fungi use effector molecules to manipulate the host cell metabolism to allow plant tissue invasion. Some small secreted proteins (SSPs) have been identified as fungal effectors in both ectomycorrhizal and arbuscular mycorrhizal fungi, but it is currently unknown whether SSPs also play a role as effectors in other mycorrhizal associations. Ericoid mycorrhiza is a specific endomycorrhizal type that involves symbiotic fungi mostly belonging to the Leotiomycetes (Ascomycetes) and plants in the family Ericaceae. Genomic and RNASeq data from the ericoid mycorrhizal fungus Oidiodendron maius led to the identification of several symbiosis-upregulated genes encoding putative SSPs. OmSSP1, the most highly symbiosis up-regulated SSP, was found to share some features with fungal hydrophobins, even though it lacks the Pfam hydrophobin domain. Sequence alignment with other hydrophobins and hydrophobin-like fungal proteins placed OmSSP1 within Class I hydrophobins. However, the predicted features of OmSSP1 may suggest a distinct type of hydrophobin-like proteins. The presence of a predicted signal peptide and a yeast-based signal sequence trap assay demonstrate that OmSSP1 is secreted during symbiosis. OmSSP1 null-mutants showed a reduced capacity to form ericoid mycorrhiza with Vaccinium myrtillus roots, suggesting a role as effectors in the ericoid mycorrhizal interaction.